A STUDY OF THE INTERACTION OF STRONTIUM IONS IN AQUEOUS SOLUTION WITH THE SURFACES OF CALCITE AND KAOLINITE - 1. X-RAY PHOTOELECTRON SPECTROSCOPIC STUDY - Parkman R.H.; Charnock J.M.; Livens F.R.; Vaughan D.J. (My University, 1998)
The interaction of Sr2+ ions in aqueous solution with the surfaces of calcite and kaolinite have been studied by exposing powdered samples of these minerals to solutions containing a range of dissolved Sr2+ concentrations. These experiments involved measuring the amounts of Sr2+ taken up from solution as a function of initial Sr2+ concentration and studying the reacted solids using scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDS) and, in particular, X-ray absorption spectroscopy (XANES and EXAFS). For calcite, very little Sr2+ is removed from solutions where initial concentrations are less than 0.3 mmol/L, but at higher concentrations, uptake increases linearly with initial Sr2+ concentration. Such behaviour, along with thermodynamic considerations, suggests precipitation of strontianite at these higher concentrations, and this was confirmed by X-ray absorption spectroscopy. The Sr K-edge X-ray absorption near edge structure (XANES) spectrum closely resembles that for strontianite, and the extended X-ray absorption fine structure (EXAFS) spectrum yields a Sr-O bond distance of 2.58 #9, very close to the value in pure strontianite (2.59 #9). Studies of such samples by SEM/EDS also suggest that a strontianite phase precipitates as a coating on the surface of the calcite. At lower concentrations of initial Sr2+ (<0.3 mmol/L), the Sr K-edge XANES spectrum does not resemble the strontianite spectrum but is similar to the Ca K-edge of Ca2+ in calcite, suggesting that Sr2+ substitutes for Ca2+ in sites at the calcite surface. The EXAFS data for such samples indicate a coordination number slightly higher than 6, possibly because Sr2+ is sorbed as a partially aquated species. The uptake of Sr2+ by kaolinite contrasts with calcite in that greatest uptake occurs when initial Sr2+ concentrations are low. The EXAFS spectra for samples with the lowest initial Sr2+ concentrations suggest that the Sr2+ is taken up as a partially aquated species into octahedral sites on the kaolinite surface. At higher concentrations, the EXAFS data show longer average Sr-O bond distances suggesting weaker binding of Sr2+ to the kaolinite surface.